Association Between Non-invasive Diagnostic Methods of Liver Fibrosis and Type 2 Diabetes in Pediatric Patients With Non-alcoholic Fatty Liver Disease - Yang, Aram; Jung, Nayoung; Kim, Sinae; Lee, Ji-Eun (Frontiers in Pediatrics, 2022)
Background/purpose: The prevalence of non-alcoholic fatty liver disease (NAFLD) in children has been increasing associated with insulin resistance. However, there is a scarcity of related studies in children with NAFLD with type 2 diabetes mellitus (T2DM) compared to adults. We conducted this study to investigate the association between noninvasive diagnostic methods of liver fibrosis and T2DM in pediatric patients with NAFLD. Methods: We enrolled a total of 152 patients aged <18 years with NAFLD, and compared their data according to the presence of T2DM. We evaluated fibrosis by transient elastography (TE, FibroScan®), and calculated the following fibrosis scores for each patient: NAFLD fibrosis score (NFS), AST:platelet ratio index (APRI), Fibrosis-4 (FIB-4) index, and pediatric NAFLD fibrosis index (PNFI). Results: In the NAFLD–T2DM group, the NFS and mean controlled attenuation parameter in FibroScan were significantly higher than those in the nondiabetic group. The receiver operating characteristic (ROC) curve values for predicting the presence of T2DM were 0.78 for NFS, 0.64 for FIB-4, 0.62 for PNFI, and 0.61 for APRI. The cutoff HbA1c levels for predicting fibrosis progression in APRI, NFS, and PNFI were 5.7% (area under the curve [AUC] 0.74), 6.4% (AUC 0.71), and 6.4% (AUC 0.55), respectively. In the multivariate analysis, hepatosteatosis on abdomen sonography, NFS, FibroScan F, and APRI were independently associated with T2DM risk. Conclusions: We significantly characterized noninvasive fibrosis markers and elastography in pediatric NAFLD with T2DM compared with the nondiabetic group. We suggest evaluating the progression of fibrosis in the prediabetic stage in children using a combination of these noninvasive methods.